If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -12 = 3x + 10 Reorder the terms: -12 + 7x = 3x + 10 Reorder the terms: -12 + 7x = 10 + 3x Solving -12 + 7x = 10 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -12 + 7x + -3x = 10 + 3x + -3x Combine like terms: 7x + -3x = 4x -12 + 4x = 10 + 3x + -3x Combine like terms: 3x + -3x = 0 -12 + 4x = 10 + 0 -12 + 4x = 10 Add '12' to each side of the equation. -12 + 12 + 4x = 10 + 12 Combine like terms: -12 + 12 = 0 0 + 4x = 10 + 12 4x = 10 + 12 Combine like terms: 10 + 12 = 22 4x = 22 Divide each side by '4'. x = 5.5 Simplifying x = 5.5
| x-2y+3x+y= | | 3x-2x+4x= | | 4m+2=2m+9 | | 2x+5=x+8 | | 5y=3y+12 | | 5x+4=7x-4 | | 14x+8y=102 | | 102=x*14+y*8 | | k^2x-k^2+x=2kx-3k+2 | | 3(f+7)=24 | | 7x-8x+12-7tx=49 | | 25(68)-7w=800 | | 3p-5=7+9p | | 2x+124321+1245x=-2x | | 2x+3=4(x-1)+1 | | 5x+6x=10x | | 1.5x-32=58 | | 2(x-3)+1(2x-5)=5 | | ln(x+3)+ln(x+1)=ln(x+7) | | 8x-7y-(3-6y)=0 | | 5(x+2)-3x=18 | | 11z-15z= | | E(x)=2 | | 10x+3=2(3x-2)+3(2x-3) | | 7-2w=-1 | | 6(x+3)=x+3(4-x) | | 3(x)-2=4 | | (6-t)(5-2t)=0 | | 4-x=0 | | -1+9(x^2)=0 | | -5-2x=0 | | -7-4x=0 |